The Modeling of Leachate Distribution Potential in Rasau Jaya Landfill - R.M Rustamaji; Fitriana Meilasari; Hendri Sutrisno (Jurnal Inovasi Teknologi, 2021)
Rasau Jaya landfill applies an open dumping system. That system results in leachate that potential to cause environmental pollution. One of the efforts that can anticipate this problem is modeling the leachate distribution patterns. This study aimed to model the potential of leachate distribution below the surface both vertically and horizontally. The using method in this study to model leachate distribution patterns is the Wenner configuration geoelectric method. Results showed that the indicated leachate spread 30 m to the northeast and 30-40 m to the southwest. The most in-depth indication of leachate distribution is up to a depth of 20.3 m